Laparoscopic versus open surgery for complicated appendicitis: a randomized controlled trial to prove safety - Thomson, John-Edwin (My University, 2015)
Background To date, no randomized control trial has been performed comparing open appendicectomy (OA) to laparoscopic appendicectomy (LA) in complicated appendicitis. A systematic review and meta-analysis in 2010 concluded LA is advantageous to OA with less surgical site sepsis in complicated appendicitis; however, the level of evidence is weak (level 3a). The aim of the study was to determine whether LA is safe in the treatment of complicated appendicitis. Methods One hundred and fourteen patients were randomized prospectively to either OA or LA using a computer generated blind method. Patients who were either less than 12 years of age, had previous abdominal surgery or were pregnant were excluded. A team of senior surgeons capable of doing both OA and LA performed all procedures. Primary outcome included all-cause mortality and procedure-related mortality; secondary outcomes included intra-operative duration, rates of wound sepsis and re-intervention, length of hospital stay and re-admission rates. The trial was registered with Current Control Trials (ISRCTN92257749). Results The intra-operative duration, the rate of wound sepsis, the number of re-operations, the length of hospital stay and the rate of re-admissions between the OA and LA groups did not differ statistically. Conclusion Laparoscopic appendicectomy is safe in complicated appendicitis.
A dissertation submitted to the Faculty of Medicine, University of Witwatersrand, Johannesburg for the Degree of Master of Medicine
Keywords: Laparoscopy; epidemiology; Appendicitis